Dicholine succinate, the neuronal insulin sensitizer, normalizes behavior, REM sleep, hippocampal pGSK3 beta and mRNAs of NMDA receptor subunits in mouse models of depression - Cline, Brandon H.; Costa-Nunes, Joao P.; Cespuglio, Raymond; Markova, Natalyia; Santos, Ana I.; Bukhman, Yury V.; Kubatiev, Aslan; Steinbusch, Harry W. M.; Lesch, Klaus-Peter; Strekalova, Tatyana (Frontiers in Behavioral Neuroscience, 2015)
Central insulin receptor-mediated signalling is attracting the growing attention of researchers because of rapidly accumulating evidence implicating it in the mechanisms of plasticity, stress response and neuropsychiatric disorders including depression. Dicholine succinate (DS), a mitochondrial complex II substrate, was shown to enhance insulin-receptor mediated signaling in neurons and is regarded as a sensitizer of the neuronal insulin receptor. Compounds enhancing neuronal insulin receptor-mediated transmission exert an antidepressant-like effect in several pre-clinical paradigms of depression; similarly, such properties for DS were found with a stress-induced anhedonia model. Here, we additionally studied the effects of DS on several variables which were ameliorated by other insulin receptor sensitizers in mice. Pre-treatment with DS of chronically stressed C57BL6 mice rescued normal contextual fear conditioning, hippocampal gene expression of NMDA receptor subunit NR2A, the NR2A/NR2B ratio and increased REM sleep rebound after acute predation. In 18-month-old C57BL6 mice, a model of elderly depression, DS restored normal sucrose preference and activated the expression of neural plasticity factors in the hippocampus as shown by Illumina microarray. Finally, young naïve DS-treated C57BL6 mice had reduced depressive- and anxiety-like behaviours and, similarly to imipramine-treated mice, preserved hippocampal levels of the phosphorylated (inactive) form of GSK3 beta that was lowered by forced swimming in pharmacologically naïve animals. Thus, DS can ameliorate behavioural and molecular outcomes under a variety of stress- and depression-related conditions. This further highlights neuronal insulin signalling as a new factor of pathogenesis and a potential pharmacotherapy of affective pathologies.